2011
DOI: 10.1510/icvts.2010.243782
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation postcardiac surgery: a common but a morbid complication☆☆☆

Abstract: Despite all the modern anti-arrhythmic drugs, the incidence of AF remains unchanged. Patients who develop AF postcardiac surgery show a significantly worse outcome compared to those without AF. This study also highlights the importance of anticoagulation in AF to prevent the devastating consequences as a result of a cerebral stroke. We believe that not only immediate treatment of AF postoperatively should be implemented, but also measures should be taken to identify the risk factors of AF and to prevent AF pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 21 publications
4
42
0
Order By: Relevance
“…The cumulative burden on the health care system is large because the average length of hospital stay is prolonged by 1 to 2 days and the cost per patient is increased by $10,000, resulting in a cumulative financial impact in the United States of 4 billion dollars per annum. 3,4 Our study found similar increases in the common complications of prolonged length of stay, increased renal failure, and need for additional medications.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The cumulative burden on the health care system is large because the average length of hospital stay is prolonged by 1 to 2 days and the cost per patient is increased by $10,000, resulting in a cumulative financial impact in the United States of 4 billion dollars per annum. 3,4 Our study found similar increases in the common complications of prolonged length of stay, increased renal failure, and need for additional medications.…”
Section: Discussionsupporting
confidence: 67%
“…2 The average hospital stay is prolonged 1 to 2 days, and patients have an increased risk of early death. 3,4 The 30-day and 6-month mortality risk is increased 2-fold in patients who experience postoperative atrial fibrillation (POAF). 3,5 The extra time in the hospital and necessary interventions result in increased costs of approximately $10,000 per patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with increased post-operative morbidity, mortality, and significantly worse long-term outcomes [3], [4], [5], [6]. The make-up or existence of any predisposing atrial substrate for POAF remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the short term, POAF results in a significantly longer stay in the intensive care unit (ITU) and in hospital, an increase in resource utilisation and an increase in the financial cost of healthcare 3–5. In the long term, new-onset POAF has a significant negative impact on survival following both valvular and coronary surgery,6 7 with a 10-year mortality up to 48% higher in patients developing POAF compared with those who do not 8. Furthermore, recent evidence suggests that correction of AF may significantly reduce the composite risk of cardiac death and major events 9…”
Section: Introductionmentioning
confidence: 99%